2017
DOI: 10.1021/acsnano.7b06524
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Dynamics of Accumulation of Systemically Injected Liposomes in the Skin by Intravital Microscopy

Abstract: Accumulation of intravenously injected cytotoxic liposomes in the skin induces serious toxicity. We used single time point and longitudinal intravital microscopy to understand skin accumulation dynamics of non-PEGylated and PEGylated liposomes after systemic injection into mice. Non-PEGylated egg phosphatidylcholine (PC) liposomes showed short circulation half-life (1.3 h) and immediate aggregation in the blood, with some aggregates lodging in skin microvasculature soon after the injection. At 24 h, and more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…Of greater relevance to this study, AmB liposomes with size < 100 nm showed extra-vasation at the inflammatory site of infection [ 22 ]. Additionally, small-sized nanoparticles have exhibited maximum deposition of their content in the skin dermis following topical application [ 43 ], and intravenously administered small nanoparticles have facilitated targeting of macrophages residing in the skin [ 43 , 44 , 45 , 46 ]. Small-sized nanoparticles (<100 nm) have also been reported to enable greater cell uptake, skin permeation and immune-targeting—all desirable properties in formulations for topical CL treatment [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of greater relevance to this study, AmB liposomes with size < 100 nm showed extra-vasation at the inflammatory site of infection [ 22 ]. Additionally, small-sized nanoparticles have exhibited maximum deposition of their content in the skin dermis following topical application [ 43 ], and intravenously administered small nanoparticles have facilitated targeting of macrophages residing in the skin [ 43 , 44 , 45 , 46 ]. Small-sized nanoparticles (<100 nm) have also been reported to enable greater cell uptake, skin permeation and immune-targeting—all desirable properties in formulations for topical CL treatment [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reactive macrophages may not necessarily reside in patients' lungs, and responses may arise from a subpopulation of Kupffer cells and/or splenic macrophages, or even other immune cells such as lung dendritic cells (Dams et al, 2000;Moghimi, 2018). Recently, we demonstrated that a significant fraction of intravenously injected liposomes, regardless of their composition, rapidly accumulate in F4/80 1 skin phagocytic cells (Griffin et al, 2017). Therefore, it is plausible that responsive skin macrophages could play a role in adverse cutaneous reactions as well as desensitization to nanomedicines.…”
Section: Innate Immunity and Nanoparticle Performancementioning
confidence: 92%
“…Interestingly, recently developed techniques detected free PEG or PEG-conjugates in tissues and plasma [ 168 , 169 ] and can be used to quantify pharmacokinetics and tissue distribution to identify at risk tissues before moving into first-in-man studies. Furthermore, a study from Griffin et al employed in vivo intravital microscopy to begin to understand the skin accumulation and toxicity of non-PEGylated and PEGylated liposomes after systemic injection into mice [ 170 ]. Studies such as this with PTs may uncover more on pharmacokinetics, aggregation, normal tissue toxicity and again, provide important information regarding future clinical application.…”
Section: Hurdle 4: Further Conceptsmentioning
confidence: 99%